About Language Tasks for teachers of English - Thornbury S. Scott (Cambridge Teacher Training and Development)
English need not only to have a good productive command of the language - they also need to know how the language works. About Language asks: 'What is it that a teacher needs to know about English in order to teach it effectively?' This book develops teachers' awareness of the language through a wide range of tasks which involve them in analysing English to discover its underlying system. The book consists of 28 units, each containing around ten tasks, plus a diagnostic introductory unit. The units start at phoneme level and progress through words, phrases and sentences on to complete texts. The language is illustrated wherever possible from authentic sources.About Language can be used by teachers in both pre-service and in-service settings. There is a full key and commentary, so that the book can be used both on training courses and for self-study.